The Urgensi Pendidikan Nilai dalam Perspektif Islam Menuju Era Society 5.0 - Maulida Zahrotul Ulya; Mukh. Nursikin (Muttaqien, 2025)
Era Society 5.0 is a civilization that emphasizes the mixing of technology and humans with the aim of achieving a comfortable life. But not only does it provide convenience, if technology is misused it can also cause various conflicts. In this regard, it is necessary to educate and inculcate values ​​such as the values ​​of truth and kindness that are in accordance with the basics of Islam so that society is able to make technology a useful thing instead of a thing that results in harm. This study aims to determine the importance of value education in an Islamic perspective in the era of society 5.0. This research is a library research where this research is carried out by using literature either in the form of books, notes or reports on the results of previous research. From this research it can be concluded that humans in this century basically live side by side with technology. In order to achieve prosperity, it is important for individuals to have a value foundation based on Islamic principles. There are at least five values ​​according to an Islamic perspective that must be instilled in individuals, namely 1) Faith and piety 2) Morals 3) Social responsibility 4) Strong character 5) Balance between academic and spiritual aspects. So value education is considered important to answer the challenges of the era of society 5.0. namely to form a harmonious community life.